The Analysis Problem based learning Use Google Sites Application for Increasing Ability of Numeracy on Gen Z Collage Students - Labiibah Shafiyyah Yaasmin; Fivi Setya Lestari; Irma Setiawati Tri Rezeki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research analyzes the application of Problem Based Learning (PBL) learning model assisted by Google Sites to improve the numeracy skills of Gen-Z collage students. This generation is known to be very familiar with technology, so the integration of digital media in learning is considered to increase their engagement and understanding. This research uses descriptive qualitative methods, data collection techniques carried out in this study are observation, interviews, questionnaires and documentation which are presented descriptively. The results showed a significant increase in collage students' numeracy skills after participating in PBL assisted by Google Sites. The application of PBL is proven to be effective for training students in problem solving and critical thinking, because it involves complex analytical processes, especially when the problems given relate to numerical data. In the context of generation Z, the utilization of Google Sites supports the enhancement of these skills, as they can easily access, collaborate and document the results of their analysis in one intuitive platform. Student responses also indicated that the use of this web-based technology can help them in understanding numeracy concepts in a deeper and more relevant way. This study concludes that the application of Problem-Based Learning assisted by Google Sites has a positive impact on the numeracy skills of Generation Z collage students. This study concludes that the application of Problem-Based Learning assisted by Google Sites has a positive impact on the numeracy skills of generation Z collage students. This approach improves students' problem-solving ability, collaboration, motivation, and numeracy skills.